Potensi ekonomi masyarakat nelayan dalam membangun ketahanan pangan berkelanjutan di Kelurahan Petoaha Kota Kendari - Jalil, Abdul; Jers, La Ode Topo; Ashmarita; Alias; Rahman, Hidayah (Jurnal Sosial Ekonomi Perikanan, 2024)
This study aims to assess the economic potential of fishing communities in building sustainable food security in Petoaha Village, Kendari City. In this study, the form of economic potential, supporting and inhibiting factors, and strategies that can be done to increase the economic potential of fishing communities were analyzed. This research used qualitative research methods. The collection techniques used included observation, interviews, and documentation. The results showed that the community utilizes fishery resources, local wisdom, social networks as a form of economic potential in supporting the community's food security system. however, limited capital and technology are inhibiting factors. In order to strengthen the economic potential of fishing communities, strategies based on cooperative development, skills education, and technology application are needed. This research provides an important contribution in building sustainable food security in Petoaha Village